Vitamin D Deficiency – A Multifaceted Impact on Bone Health and Chronic Disease Risk - Sobiński, Adam; Sadowska, Aleksandra; Welkier, Aleksandra; Miśkiewicz, Joanna; Dudek, Aleksandra; Pietrusińska, Patrycja; Moder, Jakub; Dziewierz, Anna; Kwaśniewska, Paula; Śliwa-Tytko, Patrycja (Quality in Sport, 2025)
Vitamin D is a crucial micronutrient traditionally linked to skeletal health through calcium and phosphate metabolism. However, emerging research highlights its broader physiological significance, including roles in muscle function, immune regulation, and chronic disease prevention. Despite endogenous synthesis via UVB exposure, deficiency remains a global concern due to limited sun exposure, dietary insufficiency, and certain health conditions. This review explores vitamin D metabolism, physiological functions, and clinical implications of deficiency. Evidence shows its deficiency contributes to skeletal disorders such as rickets, osteomalacia, and osteoporosis. Additionally, low vitamin D levels are associated with increased risks of autoimmune diseases (e.g., multiple sclerosis, rheumatoid arthritis, type 1 diabetes), cardiovascular diseases, metabolic disorders (e.g., type 2 diabetes), and colorectal cancer. Calcitriol, the active form of vitamin D, exhibits neuroprotective properties, suggesting potential benefits in neurodegenerative diseases like Alzheimer’s and Parkinson’s. Supplementation studies indicate improvements in bone density, muscle strength, and immune function, particularly in at-risk populations. Beyond bone health, vitamin D is integral to overall physiological function. Addressing deficiency through responsible sun exposure and tailored supplementation may mitigate chronic disease risk. Further research is essential to refine supplementation guidelines, elucidate molecular mechanisms, and integrate findings into public health strategies.